Imron Sadewo's Creativity As A Dangdut Song Creator - Dimas Bagus Setiyawan; Setyo Yanuartuti; Eko Wahyuni Rahayu; Indar Sabri; Anik Juwariyah (Jurnal Syntax Transformation, 2023)
This study aims to describe the creativity process of Imron Sadewo in song composing based on Kuntowijoyo’s biography theory, Wallas’s creativity theory and Rhodes’s creativity theory. This study uses a qualitative descriptive research method that is analyzed through three stages, namely data reduction, data display, and data conclusion. The validity test of this study is using triangulation technique and triangulation time. The results of this study indicate the creativity of Imron Sadewo in composing songs is always inspired by the background of his personal life, his relatives life and the surrounding environment. The creativity of Imron Sadewo is proven through four preparation stages; preparation, incubation, illumination and verification, also through the four creativity dimensions; person, proces, press, and product.